Case report: Condylar metastasis from hepatocellular carcinoma: An uncommon case report and literature review - Liu, Xiaojie; Liu, Yanshan; Sun, Jian; Li, Ningyi; Fan, Cunhui; Chen, Liqiang (Frontiers in Oncology, 2023)
Background： Patients with hepatocellular carcinoma are often troubled by metastases, but condylar metastasis are particularly rare. Case presentation：A 51-year-old man with the history of hepatocellular carcinoma who requested treatment for facial pain. Computed tomography indicated that the condylar bone has been destroyed and fractured. Pathology confirmed the condylar metastasis of hepatocellular carcinoma. Complete metastasectomy and condylar reconstruction was performed with the preserval of facial appearance. No local recurrence or distant metastasis was found in 8 months follow-up. Conclusion：Condyle can be a metastatic site of hepatocellular carcinoma, regardless of its rarity. Long-term comprehensive surveillance and follow up is needed for patients with hepatocellular carcinoma. The presence of solitary mass does exclude the possibility of metastatic cancer for these patients, and postoperative imaging and pathological diagnosis are important to determine its origin. If patients' physical condition permits, the mass can be completely excised and the physiological function can be restored and reconstructed.